(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
In Sumberbulu village in the Badeng Watershed, there is a community group of Songgon Pine Tourism. The initial survey on the tourism area of the Songgon Pine was a flow of surface runoff in pine forest land that flows into the Badeng River. The flow forms a natural trench with a width of ± of 10 m and a depth of ± of 2 m with a surface runoff discharge of 0.04598 m3/s indicated to carry much of the sedimentary material impacted by land erosion. Besides, there is the potential for landslides and floods in the Badeng watershed, especially in the Songgon Pine Tourism area which is affected by floods from the avalanche of the Pendil mountains of Raung volcano. Technology was applied in the form of mechanical land conservation by applying gully plugs construction. The purpose of devotion to apply the material of interlock lego brick made from bagasse ash in the form of conservation gully plugs as an effort to control land erosion. The implementation of conservation prototype construction Gully Plug from Interlock Lego Brick by empowering the community group of Songgon Pine Tourism. The composition of the mix design of Interlock Lego Brick has used a ratio of 2 TL: 3 PS: 3.5 PC: 1.5 Bagasse Ash, with the dimensions of Gully Plug construction along 10 m with a height of 50 cm and a width of 60 cm requires approximately 2000 bricks. The next stage was not only mechanical conservation buildings but also vegetative conservation in erosion-prone locations and critical land around the Badeng watershed. The sustainability program conducted by the MoU between Politeknik Negeri Banyuwangi and Perum Perhutani KPH of West Banyuwangi related to land protection in productive forest areas banyuwangi regency. — Di Desa Sumberbulu di daerah aliran Sungai Badeng terdapat Kelompok Masyarakat Wisata Pinus Songgon. Survei awal di lokasi Wisata Pinus Songgon terdapat aliran limpasan permukaan pada lahan hutan Pinus yang mengalir menuju sungai Badeng. Aliran tersebut membentuk parit alam dengan lebar ± 10 m dan kedalaman ± 2 m dengan debit limpasan permukaan sebesar 0,04598 m3/detik yang diindikasikan membawa banyak material sedimen dampak dari erosi lahan. Selain itu, terdapat potensi longsor dan bencana banjir bandang di daerah aliran sungai Badeng, khususnya di daerah Wisata Pinus Songgon yang kena dampak banjir bandang dari longsoran Gunung Pendil Pegunungan Raung. Teknologi yang diterapkan berupa konservasi lahan secara mekanik dengan menerapkan konstruksi gully plugs. Tujuan pengabdian untuk menerapkan material interlock lego brick berbahan limbah abu ampas tebu dalam bentuk konservasi gully plugs sebagai upaya pengendali erosi lahan. Penerapan konservasi prototype konstruksi Gully Plug dari Interlock Lego Brick dengan memberdayakan kelompok masyarakat Wisata Pinus Songgon. Hasil komposisi mix design dari Interlock Lego Brick menggunakan perbandingan 2 TL: 3 PS: 3,5 PC: 1,5 AAT (Abu Ampas Tebu), dengan dimensi konstruksi Gully Plug sepanjang 10 m dengan ketinggian 50 cm dan lebar 60 cm membutuhkan kurang lebih 2000 bata. Tahapan kedepannya tidak hanya bangunan konservasi secara mekanik, tetapi juga konservasi vegetatif di lokasi rawan erosi dan lahan kritis sekitar DAS Badeng. Program keberlanjutan dilakukannya MoU antara Politeknik Negeri Banyuwangi dengan Perum Perhutani KPH Banyuwangi Barat terkait perlindungan tanah di kawasan hutan produktif Kabupaten Banyuwangi.